(3JMaI GdCMHGH aj eGgjI GdfHGJ hGdCYTGHs
(3ChdgG (B:s
(3GdMeO ddg NGdb GdHTQ agPG JaSjQ HYV GdCOhjI hGdYbGbjQ GdoeHgeI GdUYHI GdZQjHI, LeYJgG eeG gh eTghQ ef cJH GdMceGA, hde CVY aj gPG GdcJGH EdG eG gh Ydjg GdYed Hjf jOj CUMGH GdhbJ ef GdoeJWHHjf s
(3BNQgG (B:s
(3hgh GdfYeGf GdCHjV GdMHS GdLHdj s
(3Vef eLehY s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B45 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(1502 (3O(B/1) s
Keywords: (3GdWHs